THE CONCEPTUAL AND TERMINOLOGICAL FIELD FOR THE PROBLEM OF ADOLESCENTS’ EXCESSIVE INVOLVEMENT INTO SOCIAL NETWORKING - Lebedynets-Roda, Olesya (PSYCHOLOGICAL JOURNAL, 2020)
The article examines the impact of social networking on adolescents’ mental health. In the modern conditions, the Internet and social networking have become an integral part of every adolescent’s life. Informational communicative technologies have been organically “built into” the social situation of modern adolescents’ development. Social networking and the Internet bring developmental opportunities, as well as are a source of risks for adolescents’ mental health. The problem of violence and excessive involvement is recognized as the most important negative social factor. The article considers the conceptual and terminological field of the problem of adolescents’ excessive involvement into social networking. The concepts of “involvement”, “involvement into social networking”, “adolescents’ excessive involvement” and “addiction” are discussed. The types of adolescents-users of social networks (“creators”, “critics”, “collectors”, “public workers”, “consumers” and “inactive ones”) and the types of adolescents’ involvement into social networking are outlined. These types of adolescents’ involvement into social networking are the following: self-presentation; social networking as an attribute of an adolescent’s image; satisfaction of the need for communication; participation in social life; self-presentation as a goal; self-affirmation based on a number of “friends”; existing problems with self-concept. Basing on the reviewed psychological and pedagogical literature, we identified three levels of adolescents’ involvement into social networking (daily, active, or excessive). The analyzed scientific works outlined the main factors contributing to adolescents’ excessive involvement and, later, dependence on (addiction to) social networking and the Internet. The risks of adolescents’ excessive involvement into social networking (harmful network content and communications, consumer and electronic (cyber) risks and Internet addiction) are examined. The two types that pose the greatest threat to adolescents’ mental health have received a closer and detailed attention. These two types are communicative risks and addiction to social networking. The typical scenarios having communicative risks, such as cyberbullying and grooming, are described.